Simulation Study on Hypervelocity Penetration of Lab Scaled Shape Charge Mechanism - Khairul H Kamarudin; Ahmad Mujahid Ahmad Zaidi; Ahmad Humaizi Hilmi; Mohamad Faizal Abdullah; Norazman M. Nor; Ariffin Ismail; Mohammed Alias Yusof; S. Rasool Mohideen (Journal of Engineering and Technological Sciences, 2022)
Shaped charge (SC) is a mechanism used by defence industries as anti-armored weapon to penetrate armored plates.  Numerous studies have been conducted on the shaped charged effects.  However, experimental studies are limited due to great safety requirement and limited access to high grade explosive.  Due to these limitations, an experimental study on a small-scale shaped charge mechanism (SCM) penetration blast test was conducted against five (5) types of target materials.  The experimental data is then verified by simulation to proof that it can be used to predict the SC penetration data. This paper intent to present a comparative study on the effect of shaped charge blast conducted by simulation with the actual experimental results. In order to conduct this study, a 2D AUTODYN software were used to develop the SC blast model against five (5) types of target materials.  This study concludes that the 2D AUTODYN simulations results can predict the hypervelocity penetration for all target materials compared to the experimental test with an average difference of 9.1 %.